Calcitonin gene-related peptide protects from soluble fms-like tyrosine kinase-1-induced vascular dysfunction in a preeclampsia mouse model - Mishra, Akansha; Betancourt, Ancizar; Vidyadharan, Vipin Alukkal; Blesson, Chellakkan Selvanesan; Belfort, Michael; Yallampalli, Chandra; Chauhan, Madhu (Frontiers in Physiology, 2023)
Introduction: Preeclampsia (PE) is a hypertensive disorder of pregnancy associated with elevated levels of soluble FMS-like tyrosine kinase (sFLT-1) and increased vascular sensitivity to angiotensin II (ATII). Calcitonin gene-related peptide (CALCA) is a potent vasodilator that inhibits the ATII-induced increase in blood pressure and protects against ATII-induced increases in oxidative stress through a mitochondrial-dependent pathway in male mice. In rodent pregnancy, CALCA facilitates pregnancy-induced vascular adaptation. Most of the vascular effects of CALCA are mediated by vascular smooth muscle cells (VSMCs). We recently reported that CALCA treatment inhibits sFLT-1-induced decreases in cAMP synthesis in omental artery smooth muscle cells (OASMCs) isolated from pregnant women and has relaxant effects in omental arteries (OA) isolated from pregnant women with preeclamptic (PE) pregnancies. The current study was designed to assess the effects of sFLT-1 on mitochondrial bioenergetics in OASMCs isolated from pregnant women in the presence or absence of CALCA and to assess the development of vascular dysfunction in sFLT-1 using a mouse model of PE pregnancy.OASMCs were isolated from pregnant women to assess the effects of sFLT-1 on mitochondrial bioenergetics and oxidative stress using the Seahorse assay and quantitative PCR. Pregnant mice overexpressing sFLT-1 via adenoviral delivery were used to assess the effects of CALCA infusion on the sFLT-1-induced increase in blood pressure, ATII hypersensitivity, fetal growth restriction, and elevated albumin-creatinine ratio. Systemic blood pressure was recorded in conscious, freely moving mice using implantable radiotelemetry devices.CALCA inhibited the following sFLT-1 induced effects: 1) increased oxidative stress and decreased oxygen consumption rate (OCR) in response to maximal respiration and ATPsynthesis; 2) increases in the expression of mitochondrial-enzyme complexes in OASMCs; 3) increased mitochondrial fragmentation in OASMCs; 4) decreased expression of mitophagyassociated PINK1 and DRAM1 mRNA expression in OASMCs; and 5) increased blood pressure, ATII hypersensitivity, fetal growth restriction, and the albumin-creatinine ratio in sFLT-1overexpressing pregnant mice.CALCA inhibits sFLT-1 induced alterations in mitochondrial bioenergetics in vascular smooth muscle cells and development of maternal vascular dysfunction in mouse model of PE.